Layanan Bimbingan Konseling Karier Bagi Pengambilan Keputusan Meniti Karier Siswa - Lilis Ermindyawati; Audry Prima (Sekolah Tinggi Teologi Nusantara, 2020)
There are still many students who plan their careers unrealistically, they make career plans based solely on their desires which are not adjusted to their abilities. The purpose of this study was to determine the effect of career guidance counseling services on career decision making for students in the State Public High School. The research method is descriptive qualitative and quantitative methods. Based on the results of the analysis of the data that has been processed shows that career counseling guidance services for making career decisions for students in the State Vocational High School are well implemented.